MEMELIHARA KEARIFAN LOKAL MELALUI WASTRA NUSANTARA - Yufenti Oktafiah; Dwi Budiarti; Dwita Laksmita Rachmawati (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Batik is a pictorial Indonesian cloth which is made specifically by writing the night on the cloth, then the processing is processed in a certain way which has a uniqueness as a whole technique, technology, as well as the development of related motifs and culture, has been designated by UNESCO as a Humanitarian Heritage for Oral and Cultural Heritage. Nonbendawi (Masterpieces of the Oral and Intangible Heritage of Humanity). Batik from time to time continues to develop with various techniques. Wastra Nusantara is the development of batik which is better known as shibori. High creativity will determine the results of the shibori produced. Shibori himself can use folding, turning, sliding or other techniques according to the creativity or desire of the maker, so that the archipelago can produce abstract motifs, boxes, lines and others. Students as the younger generation are a very inspiring and imaginative field for works of art, so that with this Community Service Activity (PKM) it is hoped that existing local wisdom can be well preserved and will not become extinct